MENINGKATKAN KUALITAS BELALAR MENGAJAR DI SDN SUKAJADI DENGAN PENERAPAN COOPERATIVE LEARNING TEKNIK KEPALA BERNOMOR STRUKTUR PADA SEMESTER GENAP TAHUN PELAJARAN 2014/2015 - -, Nuraeni (Universitas Pendidikan Indonesia, 2016)
Research carried out around Bandung took the title of improving the quality of teaching and learning in SDN Sukajadi with the implementation of cooperative learning techniques Numbered Head Structure in even semester of the school year, 2014/2015. with the problems that will look for solutions to solve in this study is: How can the application of Cooperative Learning Techniques Numbered Head structure to improve the quality of teaching and to learn in SDN Sukajadi even semester of 2014/2015. And through the application of Cooperative Learning Techniques Numbered Head structure can improve the quality of teaching and learning in SDN Sukajadi even semester of 2014/2015 ?.The objectives to be achieved in this research is to determine the extent of the application of cooperative learning techniques Numbered Head structure to improve the quality of teaching and learning in SDN Sukajadi even semester of 2014/2015. The fact proves that the Cooperative Learning Techniques Numbered Head structure can enhance the professional skills of teachers because the Cooperative Learning Techniques Numbered Head structure is able to clarify the duties of teachers in implementing the learning process that will always develop teachers in performing their professional tasks.